Comparative Life Cycle Assessment (LCA) on battery electric and combustion engine motorcycles in Taiwan. (20th June 2023) - Schneider, Falk; Castillo Castro, Daniel Sebastián; Weng, Kuo-Che; Shei, Cheng-Hsiang; Lin, Hsin-Tien
Abstract: Electric motorcycles are increasingly replacing combustion engine motorcycles, especially in Asia where personal motorcycles represent a significant proportion of the traffic share. Yet, the life cycle environmental performances of electric and combustion driven motorcycles have not yet been established with field data from this region. To enable the clarification of environmental impact from this modal shift, this study conducts a comparative Life Cycle Assessment on the most popular electric and combustion engine motorcycle models in Taiwan in SimaPro using selected impact categories from the ReCiPe impact methodology. This research reveals a burden shifting between impact categories and life-cycle stages. Electric motorcycle achieves lower impacts than combustion engine motorcycle in global warming and fossil resource scarcity, while combustion engine motorcycle outperforms electric motorcycle in freshwater eutrophication and mineral resource scarcity. Electric motorcycles obtained partially better results from the operation stage at a generally higher production impact compared to combustion driven motorcycles. To mitigate the higher impacts in electric motorcycles, increasing the recycling content in raw materials and establishing suitable reuse, repair and recycling system are suggested. A sensitivity analysis revealed significant fluctuations in conventional motorcycles and robust results for the electric motorcycle. Graphical abstract: Image 1 Highlights: Comparative LCA on modern electric and combustion engine motorcycles. Novel life cycle inventory for mid-range motorcycles from disassembly. Burden shifts between impact categories and life-cycle stages. Electronics such as circuit board cause major impact contributions. End-of-life stage of electric motorcycle has increased importance.